ANALISA FAKTOR-FAKTOR YANG MEMPENGARUHI PENERIMAAN DAN PENGGUNAAN APLIKASI GO-JEK MENGGUNAKAN UNIFIED THEORY OF ACCEPTANCE AND USE OF TECHNOLOGY (UTAUT) - Putri, Lovianevy Firtian Soebali; Mahendra, Irfan (Jurnal Pilar Nusa Mandiri, 2017)
Gojek Application is an android based application that is the entrance for customers to obtain services provided by PT Gojek Indonesia. This research was conducted to analyze the factors that affect the acceptance and use of the Gojek Application using United Theory of Acceptance and Use of Technology (UTAUT). This research was conducted on 50 people Gojek Application users are found in several locations of offices, malls, schools, colleges and the environment surrounding the housing in Jakarta. Based on research, it is known that the simultaneous factor performance expectancy, effort expectancy, social influence, and facilitating conditions and significant positive effect on use behavior Gojek Application. While partially, it is known that performance expectancy and social influence which has a positive and significant effect on use behavior Gojek Application. While effort expectancy and facilitating conditions not have a positive and significant effect on use behavior Gojek Application.